Scripted Thinking and Faulty Problem Representation: The Effects of Theoretical Orientation, Level of Experience, and Temporal Order Causal Judgement - Waxman, Tina Goodin; Rapagna, Socrates; Dumont, Frank (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper examines some of the sources of bias that enter into counsellors' formulations of causal hypotheses and client problem representations. First, there will be presented a brief overview of attribulional research bearing on certain heuristics used by counsellors in the selection of data for consideration as well as certain logical errors and hazard-prone strategies that lead to erroneous or inadequate problem representation. Second, a study of the think-aloud protocols of 32 subjects, counselling psychologists, as they examined the file of one clinically diagnosable individual is presented. The strategies they employed in representing the problem of the client are examined in the light of subjects' theoretical orientation and experience. Third, the implications of the findings for the training of counselling psychologists are explored. Training exercises and procedures as well as instructional modules are suggested for attenuating the distorting effects of theoretical set, primacy-recency in data presentation, mood and affect in the clinician, and the manifold pitfalls of a logical character to which counsellors are prone in matters of social judgement.